2015
DOI: 10.1080/02699931.2015.1010487
|View full text |Cite
|
Sign up to set email alerts
|

Threat perception after the Boston Marathon bombings: The effects of personal relevance and conceptual framing

Abstract: We examined how the Boston Marathon bombings affected threat perception in the Boston community. In a threat perception task, participants attempted to “shoot” armed targets and avoid shooting unarmed targets. Participants viewing images of the bombings accompanied by affectively negative music and text (e.g., “Terror Strikes Boston”) made more false alarms (i.e., more errors “shooting” unarmed targets) compared to participants viewing the same images accompanied by affectively positive music and text (e.g., “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 28 publications
2
33
1
Order By: Relevance
“…It is also possible that participants at Time 1 experienced greater direct exposure to the bombings than participants at the latter two time points and that exposure interacted with the anger induction to influence threat perception. Consistent with this reasoning, a recent study using Boston community members revealed that how affected participants reported feeling by the bombings during the week they occurred interacted with a negative threat‐eliciting induction to produce poorer threat sensitivity on a threat perception task similar to that reported here (Wormwood et al, ). Conversely, it is possible that individuals who were more impacted by the bombings or who had more direct exposure to the bombings were less likely to participate at Time 1 because the study involved threat perception and was located in downtown Boston less than a mile from the Boston Marathon bombings.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…It is also possible that participants at Time 1 experienced greater direct exposure to the bombings than participants at the latter two time points and that exposure interacted with the anger induction to influence threat perception. Consistent with this reasoning, a recent study using Boston community members revealed that how affected participants reported feeling by the bombings during the week they occurred interacted with a negative threat‐eliciting induction to produce poorer threat sensitivity on a threat perception task similar to that reported here (Wormwood et al, ). Conversely, it is possible that individuals who were more impacted by the bombings or who had more direct exposure to the bombings were less likely to participate at Time 1 because the study involved threat perception and was located in downtown Boston less than a mile from the Boston Marathon bombings.…”
Section: Discussionsupporting
confidence: 76%
“…In the present studies, participants were asked to make simple object recognition decisions on each trial by indicating whether or not each target individual was holding a gun. However, many previous studies have utilized similar tasks but instead asked participants to make a “shoot” vs. “non‐shoot” decision instead of an object recognition decision (e.g., Correll et al, ; Unkelbach et al, ; Wormwood et al, ). It seems likely that the experience of anger would differentially impact these two kinds of behaviors (i.e., detection vs. the aggressive action of shooting).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also of interest to threat detection performance, but somewhat distinct from threat-based visual search tasks is the shooter bias paradigm (Baumann & DeSteno, 2010). Here, participants view several different urban and suburban scenes (e.g., park, train station) and have to decide whether a target individual is holding a gun or a neutral object (e.g., camera, wallet) by means of a key press (Baumann & DeSteno, 2010) or by pulling the trigger (or refraining from doing so on neutral object trials) on a realistic, wireless gun controller (e.g., Wormwood, Lynn, Feldman Barrett, & Quigley, 2016). Participants who were instructed to write about an angry memory prior to participating in the shooter bias paradigm were more likely to misidentify a neutral object as a gun than vice versa (Baumann & DeSteno, 2010), whilst participants who were asked to write about their daily routine or about a happy or other negative event (e.g., sadness or disgust) did not demonstrate a significant difference in the types of misidentification errors made.…”
mentioning
confidence: 99%